The possibility of the application of international accounting standards to strengthen the role of oil companies in the region environment - احمد رزكار علي; حمه يعقوب احمد (Journal of Economics and Administrative Sciences, 2017)
Abstract: The underlying objective of the international standard No. (6) to assist in accounting applications for the extractive industries, taking into consideration the goals and objectives contained in the sixteenth of the private International Accounting Standards criterion accounting for land, machinery and equipment, as well as Standard No. axes (38) relating to intangible assets, and in order to create a vision of a comprehensive development needs oil in order to exact evaluation of policies related to the particular needs and draw a comprehensive frameworks with respect to treatment of expenditures and revenues in the oil production industry, is also interested in Standard No. (6) within the primary objective of the year with the help of oil-producing companies in the accounting policies and procedures put that must be rely for long periods in the current changes of prices, taking into account all the environmental variables that affect the accounting evaluation and cost over the long term and changes the procedures, and that provision for large changes in oil prices and the impact on the accuracy and the integrity and fairness of the financial reports. In addition to the previously focused international standard No. (6) Applied accounting difficulties with respect to the assessment and prediction of these variables that occur on oil prices in the long term in light of the use of the total cost method, explained the standard weakness of this method in a statement the necessary tests upon which to build entrance or window includes all precautionary measures in the oil production industry and so considering that the oil resource agent resource depletion, taking into consideration the views issued by geologists and economists in the field of micro-characteristics of the oil industry production.